Conservation conflicts: Behavioural threats, frames, and intervention recommendations. (June 2018) - Baynham-Herd, Zachary; Redpath, Steve; Bunnefeld, Nils; Molony, Thomas; Keane, Aidan
Abstract: Conservation conflicts are widespread and are damaging for biodiversity, livelihoods and human well-being. Conflict management often occurs through interventions targeting human behaviour. Conservation interventions are thought to be made more effective if underpinned by evidence and a Theory of Change – a logical argument outlining the steps required to achieve goals. However, for conservation conflicts, the evidence and logic supporting different types of interventions has received little attention. Using conflict-related keywords, we reviewed trends in behavioural intervention recommendations across conflict contexts globally, as published in peer-reviewed literature. We developed typologies for conflict behaviours, intervention recommendations, and conflict frames and identified associations between them and other geographical variables using Pearson's Chi-squared tests of independence. Analysing 100 recent articles, we found that technical interventions (recommended in 38% of articles) are significantly associated with conflicts involving wildlife control and the human-wildlife conflict frame. Enforcement-based interventions (54% of articles) are significantly associated with conflicts over illegal resource use, while stakeholder-based interventions (37% of articles) are associated with the human-human conflict frame and very highly developed countries. Only 10% of articles offered "strong" evidence from the published scientific literature justifying recommendations, and only 15% outlined Theories of Change. We suggest that intervention recommendations are likely influenced by authors' perceptions of the social basis of conflicts, and possibly also by disciplinary silos. Highlights: Conservation conflicts are widespread and framed in various ways Human behaviours in conflicts are targeted by technical, cognitive, economic, enforcement and stakeholder-based interventions Intervention recommendations associate with different conflict behaviours and frames Interventions recommendations are rarely supported by strong scientific evidence or Theories of Change Author perceptions and disciplinary silos may influence both framing and intervention recommendations